2022
DOI: 10.3390/vetsci10010023
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Congenital Pulmonary Vein Stenosis with Secondary Post-Capillary Pulmonary Hypertension and Left Sided Congestive Heart Failure in a Cat

Abstract: A five-month-old, 3.8 kg intact male Maine coon cat presented for dyspnea characterized by increased respiratory effort in addition to open-mouth breathing. Thoracic radiographs showed pectus excavatum, enlarged cardiac silhouette, and generalized interstitial patterns. Echocardiography revealed normal left atrial (LA) and left ventricular dimensions. A large tubular structure, suspected to be a distended pulmonary vein (PV), was identified as draining into the LA. Severe eccentric and concentric right ventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…PVS is a rare cardiovascular disease; till date, only one veterinary case report of a Maine coon cat with congenital PVS confirmed using echocardiography and autopsy after ethical euthanasia has been reported [3]. PVS is a rare congenital or acquired cardiovascular disease, even in humans [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PVS is a rare cardiovascular disease; till date, only one veterinary case report of a Maine coon cat with congenital PVS confirmed using echocardiography and autopsy after ethical euthanasia has been reported [3]. PVS is a rare congenital or acquired cardiovascular disease, even in humans [5].…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary venous stenosis (PVS) is rare in cats and can lead to PH. However, only one previous study has reported a case of PVS and resultant PH in cats, and this diagnosis was obtained post-mortem [3]. Here, we report a case of feline PH secondary to congenital PVS and parenchymal lung disease detected using echocardiography and computed tomography (CT).…”
Section: Introductionmentioning
confidence: 92%
“…In this study, it was noted that all cats with severe HCM had increased left atrial diameter and prolonged isovolumic relaxation time. However, as one publication [23] showed, not all cases of left-sided heart failure may be manifested with left atrial and ventricular enlargement.…”
Section: Discussionmentioning
confidence: 99%